Prognostic Value of Interim Pet/Ct in Non-Hodgkin Lymphoma [Valor Pronóstico del Pet/Ct Interino en Linfoma No Hodgkin en Comparación Con Factores Pronósticos Clásicos (Ipi) y de Composición Corporal (Sarcopenia/Lipopenia)] - Mejías-Medina, S (Sociedad Medica de Santiago, 2020)
Background: The prognosis of Non-Hodgkin Lymphoma (NHL) depends on the type of lymphoma, the extension of the disease and the response to therapy. Aim: To evaluate the prognostic value of pretreatment and interim PET/ CT compared to classic prognosis factors and body composition measurement (sarcopenia, adipopenia) in patients with recently diagnosed NHL. Material and Methods: Patients with recently diagnosed NHL who had staging 18F-FDG PET/CT performed between December 2008 and August 2018 were selected. Age, gender, weight, height, B symptoms, laboratory tests, pathology, staging PET/ CT findings (Ann Arbor, number of nodal groups and extranodal sites involved, Bulky, maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis), Computed Tomography findings (psoas muscle mass index, psoas area, psoas density, subcutaneous fat index (all of them at L3 level), and Deauville score (Lugano Criteria) were recorded. The prognostic value of each of these factors was assessed using Cox multivariable regressions. Results: Of 138 NHL studied patients (median 61 y, 15-87 y, 60.4% men), 31 of them died due to the disease. The median follow-up was 39 months (1-115 months). The strongest prognostic factors were: B symptoms (p < 0.01), anemia (p < 0.01), hypoalbuminemia (p: 0.01), sarcopenia (p < 0.01), adipopenia (p < 0.01), number of node groups involved (p < 0.01), MTV (p < 0.01), and a bad response in interim PET/CT (p < 0.01). In a comparative Cox multivariable analysis, interim PET/CT was the independent variable with the highest significance (p < 0.01). Conclusions: Early treatment response assessed by interim PET/CT is the strongest prognostic factor in NHL patients. © 2020 Sociedad Medica de Santiago. All rights reserved.